Idiopathic stroke in a normal parturient. (13th September 2010) - Ibrahim, Azza G; Mohammed, Alaa
Abstract : A 34-year-old Chinese woman was admitted to the labour suite for induction of labour. She had no history of hypertension, vascular disease or coagulapathy. She was induced for less fetal movement at 38 weeks of gestation. Labour progressed smoothly, but immediately after delivery the patient had symptoms of facial neurological deficit, slurred speech and heaviness in the left side of the body. After completion of the third stage of labour, her condition soon deteriorated with left-sided facial palsy and left-sided dense hemiplegia. The patient was then transferred to the intensive care unit where an urgent CT scan was arranged for her. She was diagnosed as a case of right-sided stroke with dense left-sided hemiplegia and left facial palsy. She was placed under the care of the neurosurgical team for 2 weeks and was discharged on regular physiotherapy treatment. She had completely recovered 6 months later.